The Modern Electronic and other Technologies to Combat New Wave of Terrorism and Criminal Activities: Prof Dr. Aftab Ahmad Malik , Dr. Waqar Azeem and Dr. Mujtaba Asad - Prof Dr. Aftab Ahmad Malik (International Journal for Electronic Crime Investigation, 2023)
Terrorists are using most recent technology to launch their attacks, therefore it is important for the suffering states like Pakistan to excessively practice the recent Electronic and other devices and technologies to safeguard and combat terrorism. By boosting security, intelligence, and surveillance capacities, electronic technology is essential in the fight against terrorism. The following electronic tools and systems are frequently employed to combat terrorism. In this paper we will focus on Artificial Intelligence, Biometric, Border Security Technology, Cybersecurity, Surveillance Technology, Communication and Encryption, use of Drones, Geospatial Technology in the context of terrorism. Apart from this we discuss about the new wave of terrorist attacks from foreign nationals and refugees living in Pakistan and their modus operandi and how to combat with them using Electronic Technology. More emphasis is required to be given to the Border Security Technology. It's crucial to remember that even if these electronic technologies are useful tools in counterterrorism efforts, they must be utilized legally and with due regard for people's civil liberties, privacy, and individual rights. A multidisciplinary strategy, including collaboration between numerous agencies, intelligence sharing, international cooperation, and complete policies and plans, is frequently necessary for counterterrorism efforts to be successful. Pakistan is facing three major problem of smuggling of commodities, foreign currency, and terrorism for across boarder.